Effect of suprarenal fixation of aortic stent grafts on renal artery ostia: Assessment of morphological changes by virtual intravascular endoscopy - Sun, Zhonghua; O'Donnell, M.; Winder, J.; Ellis, P.; Blair, P. (International Society of Endovascular Specialists, 2007)
Purpose: To investigate the morphological effects of suprarenal fixation of aortic stent-grafts on the renal artery ostia (RaO) by analysis of suprarenal stent wire distribution and vascular calcification across the RaO using virtual intravascular endoscopy (VIE).Methods: Fourteen consecutive patients (11 men, mean age 75 years) from a single institution were studied following endovascular aortic aneurysm repair (EVAR) using the Zenith endograft system from September 1999 to March 2002. Imaging assessment included computed tomographic (CT) measurement of renal artery intraluminal ostial diameter and quantification and analysis of uncovered stent struts across the RaO and radiological determination of RaO calcification. Morphological changes following EVAR at 4 time-points (before and after stent-grafting, within 1 week, and at the most recent follow-up) were compared for each patient to determine whether suprarenal stent struts or RaO calcification affected intraluminal ostial diameter. Renal function was assessed by temporal measurements of serum creatinine concentration and creatinine clearance.Results: The renal ostium was distorted to variable degrees in all cases at a mean follow-up of 416.6 months. An increase in ostial diameter was identified in most patients if the right RaO was calcified when comparing the 1-week postoperative and most recent follow-up CT images (p<0.05). There was no direct relationship between the number of stent struts crossing the RaO and the morphological/dimensional changes (p>0.05). Renal function was not significantly affected.Conclusion: Patients undergoing suprarenal fixation of aortic stent-grafts experienced morphological changes of the RaO to a variable extent at midterm follow-up. Although the presence of stent struts did not significantly affect dimensional changes, the presence of calcification at the renal artery ostium may influence the development of atherosclerotic effects as a direct relationship between the calcification and ostial diameter. Future studies utilizing VIE to determine the long-term safety of this technique in these particular patients requires investigation.